The Effect of Varying Compaction Levels on Soil Dynamic Properties and the Growth of Canola (Brassica napus L.) - Ernest Owusu-Sekyere; Ying Chen (Agriculture)
Extremely low field emergence rates for canola are primarily attributed to soil compaction from field traffic during and after planting. This study aimed to determine the critical compaction level for canola emergence across different soil types. A laboratory experiment was conducted using sandy loam, silt clay, and clay soils, compacted to five levels (zero to four) using Proctor hammer drops after sowing canola (Brassica napus L.). The lab results were validated through two years of field experiments in sandy loam, applying four compaction levels (zero to three) using a tractor. Soil properties (bulk density and surface resistance) and canola growth parameters (plant emergence rate, count, height, and above-ground biomass) were measured. Zero compaction resulted in lower bulk density and surface resistance across all soil types. Laboratory results showed maximum emergence rates of 95% for sandy loam, 100% for silt clay, and 60% for clay, while field emergence rates were 63% and 87.59% in the first and second years, respectively, both at zero compaction. Recommendations include light or no compaction for sandy loam, and zero compaction for silt clay, while clay soil did not achieve the 80% emergence target at any compaction level. These results can assist agricultural producers in optimizing their seeding equipment setup and managing field traffic for canola production.